PETIK LAUT RITUAL: FROM MYTH TO FESTIVAL - Novi Anoegrajekti; Sudartomo Macaryus; Asrumi Asrumi (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
This study aims to explain the dynamics of folk tales called as myths about fisherman figures, Buyut Kalong and Buyut Sabar as parts of the implementation of Petik Laut Muncar. This ethnographic study was started by collecting data from number of literatures and data obtained from participatory observations and in-depth interviews with Muncar fishing community leaders. Data analysis was carried out continuously since the data collection stage. Data interpretation was done by interpreting each event as a cultural phenomenon that was interrelated as a whole. The results showed that the dynamics from myths to festivals involved fishing communities, community leaders, religious scholars, and the local government of Banyuwangi